THE EXPLORING EIGHTH GRADE STUDENT’S DESCRIPTIVE WRITING PROFICIENCY AT MTS NU TRATE GRESIK - Muhammad Ashfa Qolby; Masruroh, Lailatul; Pratiwi, Widya Rizky (J-Shelves of Indragiri (JSI), 2024)
This research aims to analyze students' abilities in writing texts at MTs NU Trate Gresik. The research design is qualitative descriptive research. Data was obtained from thirty(Husna, 2018)class VIII students of MTs NU Trate Gresik randomly. This research data was collected using three types of instruments. Namely with written tests, interviews and documentation. This observation aims to determine the condition of the class during learning. The interview aims to obtain data regarding factors that influence student interest. And documentation is a supporting instrument in data collection. The research results are presented in a qualitative descriptive manner. based on the analysis, the mean score of students' descriptive writing ability was 15.3, indicating good ability. Their average scores in the content category were 3.2 (good), organization 3 (fair), vocabulary 2.8 (poor), grammar 3.2 (good), and mechanics 3.1 (fair). The test results show that students find it difficult to write descriptive texts, especially with grammar rules such as simple present tense and providing detailed descriptions. Many students struggled to form complete sentences, spell correctly, and had limited vocabulary which led to the use of repetitive words in their writing.